Exploring the Relationship between Economic Indicators, Investor Distrust, and Stock Market Volatility: case study of the KASE index dynamics - Mukan, М.М.; Ahmetzhanova, A.Kh.; Mukametkaliyeva, SettingsМ.А.; Dzharikbayeva, D.T. (BUKETOV BUSINESS REVIEW, 2024)
Object: The aim of the article is to investigate the relationship between investor distrust and the overall financial stability of the Kazakhstan Stock Exchange (KASE) through a comprehensive analysis of qualitative and quantitative methods. Methods: Qualitative analysis involves examining the activities of KASE and investor relations practices, while quantitative analysis employs regression modeling to explore the impact of macroeconomic factors on KASE index volatility. Findings: In the research varying levels of investor engagement and investor relations activities in Kazakhstan were revealed with significant correlations between macroeconomic indicators such as inflation, unemployment, GDP, and KASE index volatility. Results indicate that while inflation and GDP have limited impact, unemployment significantly influences market volatility, leading to the fact that investors less actively participate in the market activities in terms of poor economic conditions. Conclusions: Insufficient investor confidence, influenced by macroeconomic conditions and financial literacy, hinders the growth of the stock market. Building trust among investors requires transparent regulations, effective governance, and investor education initiatives to foster market participation and development.